Glycolated Thiophene‐Tetrafluorophenylene Copolymers for Bioelectronic Applications: Synthesis by Direct Heteroarylation Polymerisation. Issue 9 (11th July 2019) - Parr, Zachary S.; Halaksa, Roman; Finn, Peter A.; Rashid, Reem B.; Kovalenko, Alexander; Weiter, Martin; Rivnay, Jonathan; Krajčovič, Jozef; Nielsen, Christian B.
Abstract: A series of copolymers containing a glycolated 1, 4‐dithienyl‐2, 3, 5, 6‐tetrafluorophenylene unit copolymerized with thiophene, bithiophene, thienothiophene and 1, 2, 4, 5‐tetrafluorobenzene comonomer units were designed and synthesised by direct heteroarylation polymerisation. The optical, electrochemical, electrochromic and solid‐state structural properties of the copolymers were investigated. The copolymers exhibit stable redox properties in organic solvents and promising redox properties in thin film configuration with an aqueous electrolyte. Finally, the potential of the copolymers as active materials in organic electrochemical transistors (OECTs) was assessed, and promising performance was shown as an accumulation‐mode OECT material with a peak transconductance of 0.17 mS and a good on/off ratio of 10 5 for the thiophene copolymer. Abstract : Clever design : A series of glycolated thiophene‐tetrafluorophenylene copolymers as active materials for organic electrochemical transistors were designed and synthesised by direct arylation. The materials have been investigated electrochemically, optically and in the solid state. The most promising of these materials were examined for use in biological sensing applications as an active‐channel material for OECTs and achieved promising transconductance in the order of milliamps.